A downwind-vibrating piezoelectric energy harvester under the disturbance of a downstream baffle. (1st January 2023) - Kan, Junwu; Wang, Jin; Meng, Fanxu; He, Chenyang; Li, Shengjie; Wang, Shuyun; Zhang, Zhonghua
Abstract: Wind energy harvesting using piezoelectric transduction is becoming a promising alternative for battery-free wireless electronics. To offer a promising solution for low structure reliability of Piezoelectric Wind-induced Vibration Energy Harvesters (PWVEHs) under fairly high wind speed, a Downwind-Vibrating Piezoelectric Energy Harvester under the disturbance of a downstream baffle (DVPEH) is proposed in this paper. Unlike the most existing PWVEHs of which the bluff body swung against the wind, the structure reliability of energy harvester was improved with the downstream structure of the DVPEH. A downstream baffle was introduced to adjust the working characteristics of DVPEH to avoid the disadvantage of small amplitude of downwind structure. Meanwhile, the dynamic and electrical characteristics of the DVPEH under the disturbance of a downstream baffle was explored to enhance the power generation capacity. To prove the structural feasibility and ascertain the influence of the downstream baffle, theoretical investigation, simulation, fabrication and experimental testing were conducted. The results showed that the interaction of vortex-induced vibration and galloping was induced by the downstream baffle to accelerate the oscillation of the bluff body. Besides, the distance-diameter ratio, width-diameter ratio and length ratio brought significant effects on the performance in terms of electric output and cut-in wind speed. A maximum power of 0.42 mW was achieved at the optimal load resistance of 100 kΩ with the wind speed of 16 m/s and 20 blue LEDs in series was successfully driven by the DVPEH. It was expected that this study could provide a reference for improving the structure reliability and electric output of traditional PWVEHs. Highlights: Piezoelectric wind energy harvester uses a downwind bluff body and downstream baffle. The working mode of bluff body downwind vibration is used to improve the reliability. Dual-purpose downstream baffle can accelerate and attenuate vibration of bluff body. Critical wind speed, wind bandwidth and output voltage can be adjusted by the baffle.